Towards a design of a pressure swing adsorption unit for small scale biogas upgrading at. (February 2019) - Canevesi, Rafael L.S.; Borba, Carlos E.; da Silva, Edson A.; Grande, Carlos A.
Abstract: Pressure Swing Adsorption (PSA) is a well-known commercial technique for upgrading biogas. There are many PSA units installed around the world with capacities for biogas upgrading between 400 – 15000 m 3 /day. These units consist in four columns and operate with a pressure between 3-10 bar and a regeneration pressure up to 0.1 bar. A large majority of these PSA units is packed with carbon molecular sieve (CMS) as adsorbent. We intend to demonstrate that process developments are also necessary to downscale PSA units to treat smaller scales (< 100 m 3 /day). In this work we report experimental and theoretical analysis of a PSA unit packed with CMS as selective material with variable configurations using different cycles and column arrangements. Configurations with two, three, four and six columns are evaluated using a synthetic gas mixture (40% CO2 balanced by CH4 ) and keeping the target of producing pipeline quality bio-methane.